Genetic and biochemical evaluation of eucaryotic membrane protein topology: multiple transmembrane domains of Saccharomyces cerevisiae 3-hydroxy-3-methylglutaryl coenzyme A reductase. - Sengstag, C (1990)
Both 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase isozymes of the yeast Saccharomyces cerevisiae are predicted to contain seven membrane-spanning domains. Previous work had established the utility of the histidinol dehydrogenase protein domain, encoded by HIS4C, as a topologically sensitive monitor that can be used to distinguish between the lumen of the endoplasmic reticulum and the cytoplasm. This study directly tested the structural predictions for HMG-CoA reductase by fusing the HIS4C domain to specific sites in the HMG-CoA reductase isozymes. Yeast cells containing the HMG-CoA reductase-histidinol dehydrogenase fusion proteins grew on histidinol-containing medium if the HIS4C domain was present on the cytoplasmic side of the endoplasmic reticulum membrane but not if the HIS4C domain was targeted to the endoplasmic reticulum lumen. Systematic exchanges of transmembrane domains between the isozymes confirmed that both isozymes had equivalent membrane topologies. In general, deletion of an even number of putative transmembrane domains did not interfere with the topology of the protein, but deletion or duplication of an odd number of transmembrane domains inverted the orientation of the protein. The data confirmed the earlier proposed topology for yeast HMG-CoA reductase, demonstrated that the yeast enzymes are core glycosylated, and provided in vivo evidence that the properties of transmembrane domains were, in part, dependent upon their context within the protein.